Artificial Intelligence (AI) Penguat Kinerja ASN Kalimantan Timur - Wulandari, Devi Oktaviani; Nihayati, Badi' Zulfa (Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Timur, 2025)
This study aims to assess the quality of Artificial Intelligence (AI) as a performance enhancer for Civil Servants (ASN) in East Kalimantan using the WebQual model developed. The WebQual model consists of four main aspects: ease of access, user experience, information quality, and communication integration. The research employed a quantitative descriptive approach involving 75 ASN respondents from East Kalimantan. Data were collected through a Likert scale questionnaire (1–4) comprising 48 items and analyzed using descriptive statistics and the Chi-Square test. The results indicate that, in general, AI quality is perceived as “Satisfactory” by respondents. The functional aspect (covering ease of access and user experience) obtained an average score of 3.29; the information aspect scored 3.20; and the communication and integration aspect scored 2.80. The Chi-Square analysis produced a value of 34.30, which exceeds the critical value of 12.59 at a 5% significance level. This indicates a statistically significant relationship between AI quality and ASN user satisfaction. The study concludes that high-quality AI, including ease of use, positive user experience, relevant and reliable information, and effective communication and interaction features, directly influences the improvement of satisfaction and performance among ASN in East Kalimantan. These findings support the relevance of the WebQual model in evaluating digital platforms—not only websites but also AI applications in government sectors. This study also emphasizes the importance of strengthening communication and feedback features within AI systems to optimize AI quality and ASN satisfaction.